The Role of Higher Education Institutions and Community Partnerships in Strengthening MSME Entrepreneurshi - S, Sugiharto; Shofa, Ersa Ghaidsa Tinaya; Putri, Saskia Aulia; Maharani, Firly Tiara; Uwen, Nurul Fadhla; Al Ghifari, Muhammad Haikal (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article analyzes the role of higher education institutions and community partnerships in strengthening entrepreneurship and micro, small, and medium enterprises (MSMEs). MSMEs contribute significantly to local economies but face challenges such as limited innovation, low digital skills, and weak management. Universities support MSMEs through entrepreneurship education, research, incubation programs, and community service. Meanwhile, community partnerships involving cooperatives, government, and local groups help build a collaborative ecosystem that encourages capacity development. Using a descriptive qualitative approach, this study finds that strong collaboration improves MSME competitiveness and stimulates local innovation. However, issues of coordination, funding, and technological access require integrated and continuous support.